Prolonged dual antiplatelet therapy for Chinese ACS patients undergoing emergency PCI with drug-eluting stents: Benefits and risks - Zhang, Yong; Chu, Chao; Zhong, Zhong; Luo, Yong-bai; Ning, Fei-Fei; Guo, Ning (Frontiers in Cardiovascular Medicine, 2023)
Background: In patients experiencing acute coronary syndrome (ACS), prolonged dual antiplatelet therapy (DAPT) may reduce ischemic events and increase bleeding events differently in different ethnic groups.This study aimed to examine the benefit and risk of prolonged DAPT in Chinese patients with ACS after emergency PCI with DES. Methods: This study included 2249 ACS patients who received emergency PCI. If DAPT was continued for 12 or 12–24 months, then it was classified as the standard (n=1011) or prolonged (n=1238) DAPT group. The incidence of the following endpoint events was determined and compared between the two groups: composite bleeding event (BARC 1 or 2 type bleeding and BARC 3 or 5 type bleeding) and major adverse cardiovascular and cerebrovascular event (MACCE) [ischemia-driven revascularization, nonfatal ischemia stroke, nonfatal myocardial infarction (MI), cardiac death, and all-cause death]. Results: After a median of 47 months of follow-up [47 (40, 54)], the rate of composite bleeding events was 13.2% (n=163) in the prolonged DAPT group and 7.9% (n=80) in the standard DAPT group [odds ratio (OR) 1.765, 95% confidence interval (CI) 1.332–2.338, p<0.001]. The rate of MACCEs was 11.1% (n=138) in the prolonged DAPT group and 13.2% (n=133) in the standard DAPT group (OR 0.828, 95% CI 0.642–1.068, p=0.146). The DAPT duration was further shown to be insignificantly correlated with MACCEs by the multivariable Cox regression model (HR, 0.813; 95% CI, 0.638-1.036; p=0.094). No statistically significant difference was observed between the two groups. However, the DAPT duration was a separate predictor of composite bleeding events according to the multivariable Cox regression model (HR 1.704, 95% CI 1.302–2.232, p<0.001). Compared with the standard DAPT group, the prolonged DAPT group had substantially more BARC 3 or 5 type bleeding events (3.0% vs. 0.9%, OR 3.430, 95% CI 1.648–7.141, p<0.001), and BARC 1 or 2 type bleeding events (10.2% vs. 7.0%, OR 1.500, 95% CI 1.107–2.032, p=0.008). Conclusion: The prolonged DAPT group had a considerably greater incidence of composite bleeding events than the standard DAPT group, and no statistically significant difference in the incidence of MACCEs was found between the two groups.